Clinical Characteristics and Risk of Relapse for Patients with Stage I-II Diffuse Large B-cell Lymphoma Treated in First Line with Immunochemotherapy. Issue 6 (January 2013) - Mercadal, S.; Climent, F.; Domingo-Doménech, E.; Oliveira, A.; Romagosa, V.; de Sevilla, A. Fernández; González-Barca, E.
Diffuse large b-cell lymphoma (DLBCL) is an aggressive and potentially curable lymphoma that presents itself as stage I-II in 30% of all cases. It is known that in these localized stages, 15-20% of patients treated without rituximab eventually relapse, but less data exist regarding rituximab era. We have analyzed clinico-pathological features and risk of relapse in 98 patients with I-II stage DLBCL in complete response (CR) or unconfirmed CR (CRu) after first-line treatment consisting of immunochemotherapy. Twelve patients (12.2%) eventually relapsed. Late relapse, more than two years after diagnosis, occurred in three patients, and early relapse, less than two years after diagnosis, was documented in nine patients. Median time from diagnosis to relapse was 0.61 years for patients with early relapse and 3.66 years for patients with late relapse. The second CR rate obtained was similar in the late and in early relapsing patients, being 33% versus 44% ( p = 0.072), respectively. Three-year overall survival (OS) was 22% for early relapsing patients and 33% for late relapsing patients ( p = 0.65). In conclusion, patients who are diagnosed with stage I-II DLBCL and achieve a CR/CRu with first line immunochemotherapy have a good prognosis. However, a proportion of patients relapse, and this is less frequent in patients treated with first line with immunochemotherapy. These patients have a poor prognosis.